2020
DOI: 10.2196/17320
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile Technology for Collecting Patient-Reported Physical Activity and Distress Outcomes: Cross-Sectional Cohort Study

Abstract: Background Electronic patient-reported outcome (PROs) provides a fast and reliable assessment of a patient’s health-related quality of life. Nevertheless, using PRO in the traditional paper format is not practical for clinical practice due to the limitations associated with data analysis and management. A questionnaire app was developed to address the need for a practical way to group and use distress and physical activity assessment tools. Objective Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…Furthermore, Bellamy et al [32] found high correlations between a paper-based and mobile-based scores for osteoarthritis. Different studies [11,33,34] showed a similar response to a questionnaire requested via an app and a paper-based version. These results support the validity of the EQ-5D-5L mobile app questionnaire used in this study in healthy volunteers.…”
Section: Principal Findingsmentioning
confidence: 63%
See 2 more Smart Citations
“…Furthermore, Bellamy et al [32] found high correlations between a paper-based and mobile-based scores for osteoarthritis. Different studies [11,33,34] showed a similar response to a questionnaire requested via an app and a paper-based version. These results support the validity of the EQ-5D-5L mobile app questionnaire used in this study in healthy volunteers.…”
Section: Principal Findingsmentioning
confidence: 63%
“…Older people are often less comfortable using mobile apps, and information about quality of life may be even more relevant for this group [40]. Another recommendation is to determine the use of the mobile app in long-term monitoring; for example, as a follow-up tool during or after treatment [11,31,34].…”
Section: Future Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[27,28] On the other hand, health-related applications on smart phones are repeatedly reported to be efficient in communicating between medical providers and patients. [16][17][18][19] In a recent study, a mobile application was found to be an effective tool for increasing physical activity in breast cancer survivors. [17] The authors of that report tested the efficacy of the "Walkon" application which we will also test in our present trial to obtain daily step counts and also application-based questionnaire responses to evaluate patient distress.…”
Section: Discussionmentioning
confidence: 99%
“…Online electronic questionnaires can be used for the assessment of patient-reported outcome measures (PROMs). It has been reported that the app versions of questionnaires have shown a high level of association with the paper-based questionnaires, making their use in clinical practice and for telemedicine visits feasible [21].…”
Section: Performance Of Telemedicine Examinationmentioning
confidence: 99%